Association between ACE (I/D) polymorphism and physical performance in Brazilian handballers - Silvino, Valmir Oliveira; Almeida, Sandro Soares; Apaza, Helen Matias; de Moura, Rayane Carvalho; Costa, Crislane de Moura; Ferreira, Cirley Pinheiro; Beleense, George Sales; Ribeiro, Sérgio Luís Galan; dos Santos, Marcos Antonio Pereira (International Journal of Sports Medicine, 2025)
This study investigated the association between the ACE (I/D) polymorphism and strength phenotypes in Brazilian male handball players, considering their playing position. A total of 105 male junior handball players and 92 controls were evaluated. The ACE I/D polymorphism was genotyped by conventional PCR followed by electrophoresis in agarose gel. All participants were anthropometrically evaluated and performed the standing long jump (SLJ) and medicine ball throw (MBT) tests. Athletes presented superior performance in the SLJ and MBT tests compared to the control group in all playing positions (p<0.01). No significant differences were observed in genotype or allele frequencies when comparing athletes and controls or among playing positions. However, a significant difference was observed when comparing all athletes to controls using the over-dominant model (II+DD vs. ID; p=0.035). Additionally, ID athletes had better performance in the MBT than DD players (p=0.04), athletes with II+ID and II+DD genotypes exhibited superior performance in the SLJ test (p<0.04), and ID athletes demonstrated increased height compared to II+DD counterparts (p=0.01). In conclusion, our data showed a potential association between ACE (I/D) polymorphism and overall athletic predisposition in handball players, with no association with playing position.
Keywords: angiotensin-converting enzyme; genotype; gene; strength; sports; handball